Congenital lobar emphysema in a kitten. (28th March 2017) - Blonk, M.; Van de Maele, I.; Combes, A.; Stablay, B.; De Cock, H.; Polis, I.; Rybachuk, G.; de Rooster, H.
Abstract : A five‐month‐old ragdoll cat presented with severe respiratory signs, unresponsive to medical therapy. Hyperinflation of the right middle lung lobe was diagnosed with radiography and computed tomography. Lung lobectomy following a median sternotomy led to full recovery. Histopathological analysis revealed lobar emphysema and, based on the animal's age, congenital lobar emphysema was considered the most likely diagnosis.